Barriers to the Successful Health Care Transition of Patients with Kidney Disease: A Mixed-Methods Study on the Perspectives of Adult Nephrologists - Jenny Prüfe; Lars Pape; Martin Kreuzer (MDPI AG, 2022)
The transition from paediatric to adult-based health care is a challenging period bearing a high risk of medication nonadherence and transplant loss in adolescents and young adults after kidney transplantation. Successful transition asks for the cooperation of many, not least the adult physicians. Yet little is known about their thoughts and attitudes on the transition. We conducted a cross-sectional mixed-methods study, inviting all nephrologists registered with the German Society of Nephrology. A total of 119/1984 nephrologists answered an online survey, and 9 nephrologists participated in expert interviews on transition experiences and perceived barriers. Interviews were thematically analysed. Based on the results, 30 key statements were listed and returned to participants for a ranking of their relevance. The main themes extracted are (1) available resources, (2) patient-related factors, (3) qualification and (4) preparation of and cooperation with the paediatric setting. In conclusion, it became evident that successful transition faces multiple obstacles. At the least, it asks for time, staff, and money. Rigid structures in health care leave little room for addressing the specific needs of this small group of patients. Transition becomes a topic one wants to and is able to afford.